AutoDrop: Automatic DDoS Detection and Its Mitigation with Combination of OpenFlow and sFlow - Shahzad, Faisal; Khan, Muazzam A.; Khan, Shoab A.; Rehman, Saad; Akhlaq, Monis (Future Intelligent Vehicular Technologies, 2017)
World is emerging into global village with the support of internet connectivity. With the help of this connectivity, it also made everyone subject of being compromised. Many organizations’ confidential data and numerous online services become victim of cyber-attacks. Different researches and innovations have been made for making network secure but commercial routers limit them to deploy custom security algorithms in real network. Recently, researchers succeed to innovate a novel protocol OpenFlow in Software Defined Networks. Taking advantage of this innovation we utilized OpenFlow to analyze real-time traffic, detect DDoS attack and mitigate attack. In this paper, we proposed a methodology to automatically detect different type of DDoS attacks within few seconds of occurrence using sampling techniques for continuous monitoring site-wide traffic and block attacking source with the help of OpenFlow protocol.